Current and emerging pharmacotherapies for hereditary hemorrhagic telangiectasia. (3rd August 2017) - Albiñana, Virginia; Recio-Poveda, Lucia; Zarrabeitia, Roberto; Botella, Luisa M.
ABSTRACT: Introduction : Hereditary Haemorrhagic Telangiectasia (HHT) or Rendu-Osler- Weber syndrome, is a multisystemic vascular rare disease characterized by localized angiodysplasia. It is an inherited autosomal dominant disease. The estimated prevalence is around 1 in 5, 000. Epistaxis is the most frequent manifestation, increasing from the 4th decade of life on. Many patients show severe nose bleeds which seriously interfere with the quality of life. Epistaxes are due to telangiectases on the nasal mucosa, Areas covered : This review includes our own experience of years researching to find therapeutic agents in HHT. Our strategy has been drug repurposing, or second use of already known drugs. In this context, the use of antifibrinolytics, modulators of hormonal receptors (SERMs), anti-oxidant agents, immunosuppresants and anti-angiogenic agents, tested under preclinical conditions. Expert opinion : Out of different approaches used to decrease bleeding in HHT, effective drugs currently used in the medical practice are: antifibrinolytics, and SERMs, both raloxifene and bazedoxifene, designated as orphan drugs for the EMA (European Medicine Agency). However, the emerging field of antiangiogenesis is very promising, and we hope that in a short time, topical treatment by sprays or creams will be available.